ADVANTAGES AND DISADVANTAGES OF THE APPOINTMENT OF ERICK THOHIR AS CHAIR OF THE SHARIA ECONOMIC SOCIETY FOR THE DEVELOPMENT OF SHARIA ECONOMICS IN INDONESIA - Murdani; Denna Ritonga (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
One of the things that has become a hot and endless topic of discussion on the topic of Sharia Economics is the appointment of Erick Thohir as chairman of the Sharia Economic Community. One side considers that the appointment of Erick Thohir as chairman of the Sharia Economic Society is a good thing because of the network he has both on a national and international scale, track record in business, as someone who has a structural position in government is believed to be able to facilitate the development of sharia economics in Indonesia. However, on the other hand, a number of people in the community, Erick Thohir, are weak in understanding sharia economics because they are not motivated by Islamic and Sharia education. This research is qualitative research with a descriptive approach. Researchers use research data in the form of secondary data obtained from a number of credible sources such as scientific articles, books and a number of other sources that are credible and commonly used in research. These data were analyzed using analytical tools with stages of data collection, data selection, data reduction and drawing conclusions